Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/365046
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase1 Levels in North Indian Population with Age-Related Macular Degeneration

Abstract: Aim. The aim of the study was to estimate the levels of superoxide dismutase1 (SOD1) in patients of age-related macular degeneration (AMD) and examine the role of oxidative stress, smoking, hypertension, and other factors involved in the pathogenesis of AMD. Methods. 115 AMD patients and 61 healthy controls were recruited for this study. Serum SOD1 levels were determined by ELISA and were correlated to various risk factors. Logistic regression model of authenticity, by considering SOD1 as independent variable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The antioxidant defense operates as a balanced and coordinated system (SOD and GPx and SOD and CAT). Previous clinical studies on the impact of antioxidant enzymes on AMD, differently conceived from our study, provide contradictory data, because they did not examine interaction of enzyme activities in association with AMD, as we did [ 8 , 33 , 34 ]. Some of them measured serum or erythrocytes level (not activity) of antioxidant enzymes [ 8 , 34 ] and others measured only particular antioxidant enzymes (not all three) with [ 35 , 40 ] or without TAS levels [ 33 , 34 , 37 ].…”
Section: Discussionmentioning
confidence: 84%
“…The antioxidant defense operates as a balanced and coordinated system (SOD and GPx and SOD and CAT). Previous clinical studies on the impact of antioxidant enzymes on AMD, differently conceived from our study, provide contradictory data, because they did not examine interaction of enzyme activities in association with AMD, as we did [ 8 , 33 , 34 ]. Some of them measured serum or erythrocytes level (not activity) of antioxidant enzymes [ 8 , 34 ] and others measured only particular antioxidant enzymes (not all three) with [ 35 , 40 ] or without TAS levels [ 33 , 34 , 37 ].…”
Section: Discussionmentioning
confidence: 84%
“…In all these studies, the CCL2 expression was found to be elevated suggesting that AMD pathological phenomenon are induced with inflammatory responses created by various cellular and protein responses. Additionally, we have recently demonstrated the elevated SOD1 levels in AMD as compared to controls, which also show the inflammatory response characterizing AMD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The known environmental factors include cigarette smoking, light history, aging, diet, and race [ 6 ]. The identified susceptible genes include CFH [ 7 9 ], ABCA4 [ 10 ], ApoE [ 11 ], SOD1 [ 12 ] and Cx3cr1 [ 13 ] (see reviews for more details [ 14 17 ]). The interactions of environmental risk factors and susceptible gene variants can create state of oxidative stress, inflammation, and/or hypoxia [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%